Inflammatory epithelial cytokines after in vitro respiratory syncytial viral infection are associated with reduced lung function. Issue 3 (13th September 2021) - Duan, Wenming; Cen, Yuchen; Lin, Cindy; Ouyang, Hong; Du, Kai; Kumar, Anushree; Wang, Borui; Avolio, Julie; Grasemann, Hartmut; Moraes, Theo J.
Respiratory syncytial virus (RSV) infections in early life predispose children with cystic fibrosis (CF) to more severe lung function decline in later life. The mechanisms explaining the associations between RSV and progression of CF lung disease are not clear. In this study, a human bronchial epithelial cell line and primary human nasal epithelial cells (PNECs) from individuals with CF and healthy control donors were infected with RSV. Real-time PCR, plaque assay, cytokine detection, immunofluorescence and Western blot analyses were performed. RSV is replicated to a higher degree in CF epithelial cells as compared to control cells; however, no defects in innate immune pathways were identified in CF cells. Rather, primary p.Phe508del cystic fibrosis transmembrane conductance regulator PNECs produced more cytokines after RSV infection than control cells. Moreover, interleukin-8 and tumour necrosis factor-α production post RSV negatively correlated with lung function (% predicted forced expiratory volume in 1 s) in the individuals who donated the cells. These data suggest that CF epithelium has a dysfunctional response to RSV allowing for enhanced viral replication and an exaggerated inflammatory response that ultimately may predispose to greater airway inflammation and reduced lung function. This work demonstrates an association between epithelial inflammatory cytokines after in vitro viral infection and lung function in cystic fibrosis, and reinforces the importance of studying innate immune epithelial cell function in cystic fibrosis https://bit.ly/3gDNwwo